Implementasi Supervisi Akademik dalam Meningkatkan Kualitas Pembelajaran Matematika - Chandra, Chandra; Pestalozi, Donni; Wahidin, Wahidin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the implementation of academic supervision in improving the quality of mathematics learning at a vocational high school in Lubuklinggau City. Enhancing the quality of mathematics instruction is a strategic issue at the vocational secondary level, as it is closely related to strengthening students’ numeracy skills and work readiness. This research employed a qualitative approach with a case study design. The participants consisted of the principal and mathematics teachers selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the implementation of academic supervision through systematic stages—planning, implementation, and follow-up—contributes positively to improving the quality of mathematics learning. The impact is reflected in more structured lesson planning, the application of more contextual and participatory teaching strategies, the use of formative assessment, and the development of teachers’ professional reflection. However, the effectiveness of supervision still requires strengthening in terms of needs-based analysis and the sustainability of follow-up programs. This study concludes that academic supervision conducted systematically, collaboratively, and based on teachers’ professional needs can serve as a strategic instrument for sustainable improvement of mathematics learning quality in vocational high schools. Keywords: Academic Supervision, Learning Quality, Mathematics Education, Vocational High School, Qualitative Case Study